Substantial CT radiation dose reduction does not affect the preference for CT over direct digital radiography to diagnose isolated zygomatic fractures – A study in human cadavers. Issue 4 (November 2016) - Meijer, A.; Rozema, R.; Hartman, R.; van der Duim, S.; van Minnen, B.; Krijnen, W.P.; de Groot, M.
Abstract: Introduction: Zygomatic fractures can be diagnosed with either computed tomography (CT) or direct digital radiography (DR). The aim of the present study was to assess the effect of CT dose reduction on the preference for facial CT versus DR for accurate diagnosis of isolated zygomatic fractures. Materials and methods: Eight zygomatic fractures were inflicted on four human cadavers with a free fall impactor technique. The cadavers were scanned using eight CT protocols, which were identical except for a systematic decrease in radiation dose per protocol, and one DR protocol. Single axial CT images were displayed alongside a DR image of the same fracture creating a total of 64 dual images for comparison. A total of 54 observers, including radiologists, radiographers and oral and maxillofacial surgeons, made a forced choice for either CT or DR. Results: Forty out of 54 observers (74%) preferred CT over DR (all with P < 0.05). Preference for CT was maintained even when radiation dose reduced from 147.4 μSv to 46.4 μSv (DR dose was 6.9 μSv). Only a single out of all raters preferred DR (P = 0.0003). The remaining 13 observers had no significant preference. Conclusion: This study demonstrates that preference for axial CT over DR is not affected by substantial (∼70%) CT dose reduction for the assessment of zygomatico-orbital fractures. Highlights: Preference for low dose axial CT over DR was demonstrated in a human cadaver study. Forty out of 54 observers (74%) preferred CT over DR. ∼70% dose reduction did not affect CT preference for assessment of zygomatic fractures.